Genetic Diversity of Torch Ginger (Etlingera elatior) Germplasm Revealed by ISSR and SSR Markers. (6th May 2019) - Ismail, Nor Asiah; Rafii, M. Y.; Mahmud, T. M. M.; Hanafi, M. M.; Miah, Gous
Abstract : Fifty-seven accessions of torch ginger ( Etlingera elatior ) collected from seven states in Peninsular Malaysia were evaluated for their molecular characteristics using ISSR and SSR markers to assess the pattern of genetic diversity and association among the characteristics. Diversity study through molecular characterization showed that high variability existed among the 57 torch ginger accessions. ISSR and SSR molecular markers revealed the presence of high genetic variability among the torch ginger accessions. The combination of different molecular markers offered reliable and convincing information about the genetic diversity of torch ginger germplasm. This study found that SSR marker was more informative compared to ISSR marker in determination of gene diversity, polymorphic information content (PIC), and heterozygosity in this population. SSR also revealed high ability in evaluating diversity levels, genetic structure, and relationships of torch ginger due to their codominance and rich allelic diversity. High level of genetic diversity discovered by SSR markers showed the effectiveness of this marker to detect the polymorphism in this germplasm collection.